2022
DOI: 10.4062/biomolther.2022.061
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Effect of IDF-11774, an Inhibitor of Hypoxia-Inducible Factor-1, on Melanoma

Abstract: Melanoma is one of the most aggressive skin cancers. Hypoxia contributes to the aggressiveness of melanoma by promoting cancer growth and metastasis. Upregulation of cyclin D1 can promote uncontrolled cell proliferation in melanoma, whereas stimulation of cytotoxic T cell activity can inhibit it. Epithelial mesenchymal transition (EMT) plays a critical role in melanoma metastasis. Hypoxia-inducible factor-1α (HIF-1α) is a main transcriptional mediator that regulates many genes related to hypoxia. CoCl2 is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Existing studies predominantly concentrate on proteolysis, targeting chimeras to promote HIF-1α degradation via the E3 ligase VHL [ 26 ]. As an inhibitor of HIF-1α, IDF-11774 could decrease HIF-1α and exert anticancer effects in colorectal cancer [ 19 ] and melanoma [ 15 ]. Several studies revealed that IDF-11774 decreases HIF-1a levels through multiple mechanisms, not simply by increasing VHL-mediated HIF-1α degradation in colorectal cancer models in vitro and in vivo but also by inhibiting mitochondrial respiration and increasing intracellular oxygen levels [ 19 ], or acting as a heat shock protein 70 (Hsp70) inhibitor [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies predominantly concentrate on proteolysis, targeting chimeras to promote HIF-1α degradation via the E3 ligase VHL [ 26 ]. As an inhibitor of HIF-1α, IDF-11774 could decrease HIF-1α and exert anticancer effects in colorectal cancer [ 19 ] and melanoma [ 15 ]. Several studies revealed that IDF-11774 decreases HIF-1a levels through multiple mechanisms, not simply by increasing VHL-mediated HIF-1α degradation in colorectal cancer models in vitro and in vivo but also by inhibiting mitochondrial respiration and increasing intracellular oxygen levels [ 19 ], or acting as a heat shock protein 70 (Hsp70) inhibitor [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, with the recognition of the pivotal role of HIF-1α in tumor adaptation, there is a growing landscape of cancer therapies targeting HIF-1α. IDF-11774, an orally administered HIF-1 inhibitor, emerges as a promising clinical candidate with demonstrated efficacy in various in vitro and in vivo models of colorectal, lung, and thyroid cancer [ 14 ] and melanoma [ 15 ]. The synthesis of IDF-11774 involves acid–amine coupling between 1-methyl piperazine and 4-(1-adamantyl)-phenoxy acetic acid [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HIF-1α inhibitor, IDF-11774, achieved similar results in a nude mouse B16-F10 model, diminishing tumor growth and increasing CD8 + T cell infiltration. Additionally, IDF-11774 reduced expression of the EMT markers SNAIL and N-cadherin ( 169 ). HIF-1α regulates melanoma VEGF expression, and increasing evidence supports the HIF-1α/VEGF axis contributes to metastasis and EMT ( 170 172 ).…”
Section: Immune Escape In Tumor Hypoxia and Acidificationmentioning
confidence: 99%